Association of Severity of Posttraumatic Stress Disorder With Inflammation: Using Total White Blood Cell Count as a Marker. (September 2019) - Koraishy, Farrukh M.; Salas, Joanne; Neylan, Thomas C.; Cohen, Beth E.; Schnurr, Paula P.; Clouston, Sean; Scherrer, Jeffrey F.
Background: Inflammation is known to be associated with posttraumatic stress disorder. It is not known if total white blood cell count, a routinely checked inflammatory marker, is associated with posttraumatic stress disorder symptom trajectories using medical record data. Methods: We used latent class growth analysis to identify three-year posttraumatic stress disorder symptom trajectories using posttraumatic stress disorder (PTSD) Checklist (PCL) scores. The outcome for each patient was maximum white blood cell count from index posttraumatic stress disorder diagnosis to last PCL . Using linear regression analysis, we then calculated and compared the average white blood cell count for each trajectory before and after controlling for age, gender, race, obesity, smoking, diabetes, hypertension, cardiovascular disease, depression, and other comorbid inflammatory conditions. Results: Patients were 40.2 (SD ± 13.5) years of age, 83.7% males and 67.9% white. We identified three PCL trajectory groups based on symptom severity over time: "moderate-large decrease, " "moderate-severe-slight decrease, " and "severe-persistent." In adjusted analyses, "severe-persistent" versus "moderate-large decrease" had significantly higher white blood cell count (B = 0.64; 95%CI = 0.18, 1.09; p = .006). Although non-significant, "moderate-severe-slight decrease" versus "moderate-large decrease" also had a higher white blood cell count (B = 0.42; 95% CI: −0.02, 0.86; p = .061). Conclusion: Persistently severe posttraumatic stress disorder is associated with a higher white blood cell count than improving posttraumatic stress disorder. White blood cell appears to have utility for measuring the association between psychiatric disorders and inflammation in retrospective cohort studies involving large administrative medical record data bases.